Les Esquimaux et les songes - Anzieu, Didier (Le présent de la psychanalyse, 2020)
The Eskimos’ waking dream would be to base their social organization on their nocturnal dreams. For them, it is neither gods nor unconscious desires which drive these shadowy visions. Rather, it is the construction of their own society which is at work. The Eskimos’ waking dream would be to base their social organization on their nocturnal dreams. For them, it is neither gods nor unconscious desires which drive these shadowy visions. Rather, it is the construction of their own society which is at work.